2019
DOI: 10.1002/mrd.23259
|View full text |Cite
|
Sign up to set email alerts
|

Use of pregnancy‐associated plasma protein‐A during oocyte in vitro maturation increases IGF‐1 and affects the transcriptional profile of cumulus cells and embryos from Nelore cows

Abstract: Insulin‐like growth factor 1 (IGF‐1) activity is established by the regulation of IGF binding protein activity, which blocks IGF‐1 functions, whereas pregnancy‐associated plasma protein‐A (PAPP‐A) improves IGF‐1 bioavailability and facilitates binding to IGF receptors. To further extend our understanding of the effect of exogenous PAPP‐A on bovine embryo production, we added this protein during in vitro maturation of cumulus‐oocyte complexes (COCs); moreover, we assessed its effects on IGF‐1 quantity in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…En tal sentido, IGF2, IGFR1, IGFR2 e IR están presentes en ovocitos humanos y de ratón, implicados en la regulación del desarrollo de gametos (Ipsa et al, 2019). Esta regulación difiere entre especies observándose que los ovocitos bovinos expresan dos receptores, IGFR1 e IGFR2, e IGF1 pero no IGF2 (Giroto et al, 2019). La expresión y localización de los IGF al inicio de la gestación ha sido estudiada en diferentes especies de rumiantes (cuadro 2).…”
Section: Factores De Crecimiento Con Acción Similar a La Insulina (Ig...unclassified
“…En tal sentido, IGF2, IGFR1, IGFR2 e IR están presentes en ovocitos humanos y de ratón, implicados en la regulación del desarrollo de gametos (Ipsa et al, 2019). Esta regulación difiere entre especies observándose que los ovocitos bovinos expresan dos receptores, IGFR1 e IGFR2, e IGF1 pero no IGF2 (Giroto et al, 2019). La expresión y localización de los IGF al inicio de la gestación ha sido estudiada en diferentes especies de rumiantes (cuadro 2).…”
Section: Factores De Crecimiento Con Acción Similar a La Insulina (Ig...unclassified
“…In fact, IGF-2 , IGFR-1 , IGFR-2 , and IR are present in human and mouse oocytes, where an IGF/insulin axis regulates gamete development [ 118 , 119 ]. This regulation differs between species, e.g., rat oocytes only express IGF-1 but not its receptor IGFR-1 [ 120 ], bovine oocytes express two receptors, IGFR-1 and IGFR-2 , and IGF-1 but not IGF-2 [ 121 , 122 ], and in dog, corpus luteum presents a similar amount of IGFR-1 , but expression of IGF-1 diminishes during embryonic development [ 123 ]. In vitro studies have shown that the addition of IGF-1 in culture oocyte medium improves maturation rate and embryonic development in sheep by the PI3/AKT pathways, but the blastocyst development rate is not affected in sheep and mice [ 124 , 125 , 126 ].…”
Section: Growth Factors and Early Developmentmentioning
confidence: 99%